PENGARUH CORPORATE GOVERNANCE DAN KARAKTERISTIK PERUSAHAAN TERHADAP LUAS PENGUNGKAPAN TRANSAKSI PIHAK BERELASI DI INDONESIA - Hani Werdi Apriyani (Jurnal Akuntansi Indonesia, 2015)
The purpose of this study is to examine the influence of corporate governance and firms characteristics to the extent of disclosure of related party transactions. The independent variable in this study is the level of ownership concentration, independent commissioners, the level of corporate diversification, and profitability. The dependent variable is the related party transactions disclosure. In analyzing the effect of independent variables on the dependent variable, included two control variables in our model, the type of industry and company size. The sample used in this study is annual report of non-financial companies listed in the Indonesia Stock Exchange 2008 -2011. Purposive sampling use to determine sample. There are 25 companies that meet the criteria as the sample in this study, and finally 90 annual report used in this analysis. Statistical methods using multiple linear regression analysis. The analysis showed that profitability have significant effect in Related Party Transaction disclosure. Level of ownership concentration, the level of corporate diversification , and independent commissioners did’t significantly influance the related party transaction disclosure.